Studies on In Vitro Shoot Regeneration of Tomato (Lycopersicon Esculentum Mill.) for The Development of an Agrobacterium – Mediated Transformation System - Arief, Meta Sritua (1999)
A potentially important gene (Chi2;1) isolated from a tomato pistil eDNA library (Gasser et al., 1989), showed a differential expression pattern in the transmitting tissue of the style. This finding led to the hypothesis that a gradient of promoter-binding transcription factors controlled this expression. The isolation of these transcription factors requires the identification of such promoter elements via the transformation of deleted Chi 2;1 promoter (ChiP) fragments into tomato and tobacco. This study to forms the basis for the above requirement. It focuses on the development of in vitro shoot regeneration (SR) in local tomato and Agrobacterium-mediated transformation (AMT) protocols in tomato and tobacco. The results of this study revealed the following findings: 1. Cotyledon explants of local tomato (MTI and MTII) exhibited the highest shoot regeneration (SR) efficiency (mean shoot production and mean shoot primordia eiongation) in response to applications of 3 mgl⁻¹ ZEA and 5 mgl⁻¹ KIN alone or in combination with 1 mgl⁻¹ IAA, respectively in MS medium. The SR response induced by 3 mgl⁻¹ ZEA in cV. MTII was more vigorous albeit slower than that induced by either 5 mgl⁻¹ KIN alone or in combination with 1 mgl⁻¹ IAA in cv. MTIl. 2. Infection of local tomato seedlings with wild-type A. tumefaciens and A. rhizogenes strains resulted in the induction of crown gall tumours and hairy roots of various size and length, respectively. The infection of cotyledon explants with A. tumefaciens strain GV2260 (a binary vector system with a GUS reporter gene and kanamycin-resistant gene), induced GUS-expressing callus which failed to regenerate shoots end eventually died under kanamycin (100 mgl⁻¹) selection. A lower kanamycin level (50 to 80 mgl⁻¹) is recommended to allow the survival and shoot regeneration of transformed callus. 3. The utilisation of two A. tumefaciens strains, GV2260 and LBA4404 (binary vectors) in the infection of tobacco leaf explants showed that only specific cell densities of 10⁸ and 10⁸, respectively were conducive to the regeneration of transformed shoots. Pre-culturing, infection with acetosyrlngone-traated bacterial cells, and induction of callus and shoot primordia before antibiotic selection, enhenced a significantly higher percentage and SR of GUS-positive explants in the treated explants than in the control explants. As strain GV2260 was more efficient than strain LBA4404, the conditions discovered using strain GV2260 were used in the transformation of several deleted ChiP fragments into tobacco.